Criminal Law Characteristic of Special Relapse of Bribery - A. V. Koval (Сибирское юридическое обозрение, 2018)
The article is devoted to qualification and criminal-political assessment of the qualifying sign of petty bribery - the existence of previous convictions. It is concluded that the presence of the previous conviction is a sign of the composition that characterizes the special subject of the crime, and in its legal nature this sign corresponds to the concept of actual (or criminological) relapse and covers both the actual relapse of crimes as it is defined in art. 18 of the Criminal Code of the Russian Federation, as well as other repeated cases of petty bribery by a person who has a criminal record for taking bribes, giving bribes, mediating bribery or petty bribery. The conditions for the qualification of a crime under this qualifying criterion, the questions of its application in the conditions of the retroactive force of the criminal law are described. Suggestions are made to improve the legislative regulation of the relevant qualifying circumstances, to its wider use in the system of differentiating responsibility for bribery.